Luck vs Skill in Gambling over the Recession. Evidence from Italy - Sara Capacci; Emanuela Randon; Antonello E. Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We perform an econometric analysis of the gambling market in Italy over the recession (2009-2012), observing the consumption patterns in "luck" and "skill" games. We find a different effect between the early and late period of the crisis. Whereas gambling initially behaves as normal good, in the long run luck games increase with the worsening of economic conditions. Moreover, skill games are more persistent and influence luck games, but not the opposite. Skill players choose simple lottery games, but luck players cannot handle complex games. Our results provide insights on investment choices in financial markets among expert and naïve buyers.
Keywords: D12; L83; G01; 330